Implementasi Pendekatan Berbasis Genre pada Pembelajaran BIPA Daring - Fauzi, Fakhri; Kartika-Ningsih, Harni (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2023)
Genre-based Approach (GBA) is a teaching method that has long been implemented in the English learning context as well as other foreign language learning contexts. In this study, we examined the application of GBA in an online BIPA (Bahasa Indonesia bagi Penutur Asing or Indonesian for Foreign Language Speakers) class by observing the classroom interaction patterns. The objective of this research is twofold. It is to investigate the extent to which the genre-based approach is applied and to discover the application of genre-based stages Building Knowledge of Field and Modelling in one online BIPA class. This study employed a qualitative discourse analytic method, specifically classroom discourse analysis following pedagogic register framework from systemic functional linguistics. The data were collected from the recordings of online BIPA class in two sessions, focusing on the stage of Building Knowledge of the Field and Modelling. The results indicate a variety of learning activities and a tendency of classifying a language skill to a specific stage from the GBA. These variations of activities and the classification of language skills suggest that there is a modification of the stage of genre-based approach in online BIPA class which is distinctive to that of other offline implementations.